2019
DOI: 10.1109/access.2019.2927266
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study With Imbalanced Classification Approaches for Credit Card Fraud Detection

Abstract: Credit card fraud is a criminal offense. It causes severe damage to financial institutions and individuals. Therefore, the detection and prevention of fraudulent activities are critically important to financial institutions. Fraud detection and prevention are costly, time-consuming, and labor-intensive tasks. A number of significant research works have been dedicated to developing innovative solutions to detect different types of fraud. However, these solutions have been proved ineffective. According to Cifa, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
101
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 208 publications
(102 citation statements)
references
References 39 publications
0
101
0
1
Order By: Relevance
“…Based on a small stratified initial training set, Naïve Bayes iteratively teaches its base with the instances that the model is most uncertain about. Finally, Makki et al [39] confirmed an experimental study with different solutions to deal the imbalance classification issue. They explored these adopted techniques along with the machine learning algorithms applied to fraud detection and recognized their weaknesses.…”
Section: Related Workmentioning
confidence: 83%
“…Based on a small stratified initial training set, Naïve Bayes iteratively teaches its base with the instances that the model is most uncertain about. Finally, Makki et al [39] confirmed an experimental study with different solutions to deal the imbalance classification issue. They explored these adopted techniques along with the machine learning algorithms applied to fraud detection and recognized their weaknesses.…”
Section: Related Workmentioning
confidence: 83%
“…Credit card fraud considers one of the most common aspects of electronic fraud. Therefore, many approaches introduced to handle this problem and related fields, including illegal purchased for goods and services [107][108][109]. Another example compromises to healthcare services, that individuals and criminal networks whose commit fraud for nefarious reasons, personal gain, and obtaining medicines and medical supplies to gain private benefits illegally.…”
Section: Criminal Analysis and Fraud Detectionmentioning
confidence: 99%
“…When factoring in skewness, logistic regression, C5.0 classifier, Support Vector Machines and Artificial Neural Networks have proven [33] to perform better on imbalanced data than other techniques (Naïve Bayes, Bayesian Belief Network, Artificial Immune Systems, K Nearest Neighbors). Similar research [34] concluded that neural networks can better deal with imbalanced data than Support Vector Machines, Random Forest and decision trees.…”
Section: ) Supervised Techniquesmentioning
confidence: 99%